JURIDICAL ANALYSIS OF THE PROCEDURE FOR BLOCKING LAND TITLE CERTIFICATES - Laji Siswanto; Sunardi Sunardi; Misranto Misranto (SOSIOEDUKASI, 2026)
Blocking land title certificates functions as a procedural tool in land administration to freeze existing rights during disputes or legal proceedings. Despite being robust evidence of ownership, certificates do not offer complete legal finality, as third-party claims may still arise. This normative legal research analyzes the grounding, process, and effects of certificate blocking under prevailing laws. Using statutory and conceptual approaches, it qualitatively examines primary, secondary, and tertiary legal sources. The study finds that the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation No. 13 of 2017 provides the formal legal basis for the blocking procedure. The blocking procedure is carried out through an administrative mechanism at the land office with certain requirements and time periods. The imposition of a block on a land title certificate carries specific legal consequences: it immobilizes the land register by prohibiting updates and freezes the alienability of the land rights. In this way, blocking operates as an injunctive safeguard, preserving the status quo to prevent transfers that could cause harm pending a definitive judicial determination.